An evaluation of the flip flop approach to combating terrorism and religious extremism in Nigeria from 2015-2022 - Franklin Sanubi; Ogheneakpoje Benedict Ighoshemu; Abraham Orhero (Journal of Social Studies (JSS), 2023)
The fundamental responsibility of government is to secure citizens life and properties. The ongoing terrorist activities and religious extremism in Nigeria is yet to receive the required attention from the government. In light of the growing influence of terrorism and religious extremism in Nigeria, the study adopted the relative deprivation theory, to explain possible causes of terrorism and the recruitment of terrorists. The paper examines the ideological variations among the terrorist groups, using the quantitative textual analysis of secondary data to evaluate and scrutinize the flip flop approach of the Nigeria government from 2015 to 2022 in combating terrorism and religious extremism in the country. Despite the response by government, insecurity, terrorism and religious extremism have not been defeated due to lack of political will and the inability of government to make good laws to sanction offenders, thus, endemic poverty encourages the spread of terrorism and religious extremism. The study recommend among others, the need for government to properly police the borders, religious or tribal nepotism should not be condoled and not until systematic corruption, bad governance, inter religious and ethnic rivalry aimed at the control of state apparatus for economic and political selfish gains are seriously addressed and curtailed. The paper suggests that acute poverty and relative deprivation are precursor to the serial insecurity and terrorism that Nigeria is facing today.